Legal support for information security of legal entities under Lithuanian and Ukrainian legislation - M. Pleskach; I. Tumasoniene (Law and Safety, 2023)
In the rapidly evolving digital landscape, the safeguarding of information security for legal entities has emerged as a critical concern. This article investigates and compares the legal frameworks governing information security for legal entities in Lithuania and Ukraine, addressing the pressing need to understand and enhance legal support in this field. The relevance of this research stems from the escalating challenges posed by cyber threats, necessitating a robust legal infrastructure to fortify information security. The study delves into the fundamental elements of information security as mandated by Lithuanian and Ukrainian laws. It analyses the legislative provisions, compliance requirements, and institutional mechanisms established in both jurisdictions to protect sensitive data and mitigate cyber risks faced by legal entities. A comparative analysis is conducted to elucidate the similarities, disparities, and effectiveness of the respective legal frameworks.This research employs a multifaceted methodology and scientific methods to achieve comprehensive insights. It involves an extensive review of existing legal texts and regulations pertinent to information security in Lithuania and Ukraine. Additionally, case studies and practical examples are utilized to contextualize the application and enforcement of these legal provisions. The results of this study highlight the strengths and shortcomings within the legal frameworks of both countries concerning information security for legal entities. By examining the practical implications and challenges faced by businesses in adhering to these laws, this research aims to provide valuable insights for Ukrainian and Lithuanian companies concerned with maintaining a high level of their information security.In conclusion, this article underscores the critical importance of a robust legal framework in protecting the information security of legal entities. It offers a comparative analysis of Lithuanian and Ukrainian legislation, presenting valuable findings and recommendations to fortify and harmonize legal support for information security in both jurisdictions.